Vinorelbine in Combination with Carboplatin followed by Single-agent Consolidation Therapy for Unresectable Localized or Metastatic Non-small-cell Lung Carcinomas - (:unkn) unknown (ASIAN PACIFIC ORGANIZATION CANCER PREVENTION, 2009)
Background: Adding more than four cycles of the combination regimen increase toxicities. The availability of an intravenous (i.v.) and oral form of vinorelbine appeared as a particularly convenient way to provide a consolidation treatment to patients who have achieved an objective response or stable disease. Patients and methods: This study was retrospectively designed to investigate the efficacy in terms of response and safety of i.v. vinorelbine 25 mg/m(2) on day 1 and oral vinorelbine 60 mg/m(2) on day 8 given with carboplatin area under the curve (AUC) 5 once every 3 weeks (q3w) for four cycles followed by consolidation therapy with single-agent vinorelbine in non-progressive patients with advanced non-small-cell lung cancer (NSCLC). Results: Seventy-two patients enrolled into the study from October 2006 to July 2009 received the combination regimen. Thirty-seven patients (51.3%) also received the subsequent consolidation treatment. Partial tumor responses were obtained in 25 patients (34.7%) of 72 evaluable patients. Stable disease was observed in 26 (36.1%) of patients. The median progression free-survival was 4 months (95% CI 3.1-4.8). The median overall survival time was 10 months (95% CI 8.2-11.7) and the 1 year survival was 38.1%. The main toxicities recorded were hematological. Grade 3-4 neutropenia were observed in 17 patients (23.6%). Only two patients experienced grade three febrile neutropenia in the induction period, and there was no occurrence of febril neutropenia in the consolidation period. Nausea and vomiting were the major non-hematological toxicities reported. Toxicities occurred primarily during the initial combination phase of the chemotherapy. Conclusions: Despite the low dose of vinorelbine (25mg/m(2) i.v. on day 1 and only 60 mg/m(2) oral on day 8, every 3 weeks) achieved during the study, the response rate of 34.7%, the disease control of 70.8% and the 10 months median overall survival with tolerable toxicity profile, confirmed that this combination, offers an active and safe regimen for patients with advanced NSCLC
Keywords: Non-small-cell-lung cancer; vinorelbine; carboplatin; consolidation; Turkey; PHASE-II TRIAL; ORAL VINORELBINE; CLINICAL-TRIALS; CANCER; GEMCITABINE; CISPLATIN; CHEMOTHERAPY; METAANALYSIS; EFFICACY; NSCLC